Problems in determining the nutrition declaration for unpacked meat products – example of domestic cooked sausage. (September 2019) - Raseta, M; Jovanovic, J; Brankovic Lazic, I; Trbovic, D; Mrdovic, B; Beckei, Z; Djordjevic, V
Abstract: This study aimed to determine the degree of change that unpacked pasteurized (i.e. cooked) sausages undergo during their shelf-life. For that purpose, unpacked domestic cooked sausages were examined for basic nutritional parameters, as are required to be stated on labels by local and EU legislation, at the beginning (day 1) and end of their shelf-life (day 40). Results showed the examined parameters varied significantly (the % variance range was 41.5-129.4%), which vastly exceeds the tolerance of variation limits allowed in the legislation (20-50%). The results obtained show the responsible authority would be unable to adequately control the nutrition declaration of these unpacked domestic cooked sausages. The inability to maintain the nutritional content according to the declaration of these unpacked meat products during their shelf-life is a great challenge for quality control of this type of meat product at retail.